Dinâmica de paredes de domínios em microfios amorfos recobertos por vidro - Beck, Fábio (2010)
Amorphous glass-coated microwires are materials with soft magnetic properties suitable for various technological applications, mainly magnetic sensors. One of the outstanding properties of microwires with positive magnetostriction is the magnetic bi-stability, that means, the inversion of the magnetization is done by one magnetic domain wall displacement along the wire. In this work it was developed a system to determine the domain wall speed in microwires and studied its dynamic. Particularly, were studied the relation between domain wall speed, magnetic field and magnetoelastic anisotropy in Fe77;5Si7;5B15 microwires. It has been verified that the main source of domain wall damping is the eddy-currents and spin relaxation, both with a strong relation with the magnetoelastic energy. The magnetoelastic energy is changed by the axial applied stress which, by its time, modifies the damping mechanisms. It was also verified that the domain wall damping present different behavior at low (mainly eddy-currents) and high applied stress (spin relaxation).